Health culture in the Baghdadi community: an analytical anthropological view of Baghdadi proverbs - Khalaf, Shalal (Al-Adab Journal, 2023)
The current research aims to identify Recognizing the image of health culture in the light of the popular Baghdadi proverbs Directing our gaze to the popular Baghdadi proverbs that we can benefit from Examination of the raw material, which is the many and varied examples The research was based on the method of analyzing the scientific material to be studied (Al-Baghdadi Proverbs) The research reached to the most important results Folk proverbs are a means of delivering a message in the field of healthy culture to individuals that helps them to know a lot of information about the spread of diseases and limit their confrontation. Popular proverbs for any society express the intellectual system that forms the cultural framework for them